When the Road Bends - Tales of a Gypsy Caravan - Dellal, Jasmine (Little Dust Productions, 2006)
Verzio FF Submission The documentary follows five Gypsy bands from four countries which unite for the Gypsy Caravan as they take their show on a six-week tour around North America. The film takes place in several locations in Spain, Macedonia, Romania and India, as well as in Europe and in the USA. The "Gypsy Caravan" tour extravaganza features performances by Macedonian singer Esma Redzepova, traditional Indian folk troupe Maharaja, Romanian Fanfare Ciocarlia, the violin wizardry of Romanian group Taraf de haiduks and the Antonio el Pipa Flamenco Ensemble. Their musical styles range from flamenco to brass band, Romanian violin to Indian folk. As the film follows them through the amazing performances and behind-the-scenes action, we discover the real lives of these musicians. We visit Macedonia, Romania, India and Spain, meet their families and see what music brings to their lives.